Use of disruptive technologies in Peru - Burga-Larco, Gonzalo (2020)
This paper aims to identify the perceptions of the main stakeholders of IBM about the external communication strategies that have been applied on the potential use of disruptive technologies. A qualitative methodology with a case study approach was applied. Through the homogeneous sampling technique, six semi-structured interviews with stakeholders of IBM and one focus group with 11 university students were conducted. As a result, there is interest in Peruvians to know what disruptive technologies are; however, its dissemination has a commercial focus that is not generating development or relevant solutions in the local market. It is necessary that specialists and the media disseminate information that does motivate their use in a real and effective way.